New Pilot-Plant Photo-Fenton Solar Reactor for Water Decontamination - Farias, Jorgelina (2009)
A theoretical and experimental study of a new pilot-plant solar reactor for the photo-Fenton treatment of waters containing toxic organic compounds is presented. This hybrid unit was designed and built to capture thermal and photochemical solar radiation, yielding higher degradation rates of a model pollutant. The mass and thermal energy balances and the radiative transfer equation are solved to compute the pollutant and hydrogen peroxide concentrations and the reaction temperature as a function of time. The spectral UV/visible and broadband solar radiation incident on the reactor window are estimated from a computational code: the Simple Model for the Atmospheric Radiative Transfer of Sunshine (SMARTS2) program. Under irradiated runs, an experimental temperature increase up to 25 °C is reached. Also, for a reaction time of 180 min and a relatively low iron concentration, the combined effect of UV/visible and thermal sunlight is able to degrade 98.2% of the initial pollutant concentration.